Dynamics of dual-fluorescent polymersomes with durable integrity in living cancer cells and zebrafish embryos. (June 2018) - Askes, Sven H.C.; Bossert, Nelli; Bussmann, Jeroen; Talens, Victorio Saez; Meijer, Michael S.; Kieltyka, Roxanne E.; Kros, Alexander; Bonnet, Sylvestre; Heinrich, Doris
Abstract: The long-term fate of biomedical nanoparticles after endocytosis is often only sparsely addressed in vitro and in vivo, while this is a crucial parameter to conclude on their utility. In this study, dual-fluorescent polyisobutylene-polyethylene glycol (PiB-PEG) polymersomes were studied for several days in vitro and in vivo . In order to optically track the vesicles' integrity, one fluorescent probe was located in the membrane and the other in the aqueous interior compartment. These non-toxic nanovesicles were quickly endocytosed in living A549 lung carcinoma cells but unusually slowly transported to perinuclear lysosomal compartments, where they remained intact and luminescent for at least 90 h without being exocytosed. Fluorescence-assisted flow cytometry indicated that after endocytosis, the nanovesicles were eventually degraded within 7–11 days. In zebrafish embryos, the polymersomes caused no lethality and were quickly taken up by the endothelial cells, where they remained fully intact for as long as 96 h post-injection. This work represents a novel case-study of the remarkable potential of PiB-PEG polymersomes as an in vivo bio-imaging and slow drug delivery platform.